Terrorism catastrophising and hazardous alcohol use among students of a tertiary institution in Jos, Nigeria - Okonoda, Kingsley M.; Obindo, James T.; Onifade, Peter O.; Makput, Duwap M.; James, Bawo O. (International Journal of Research in Medical Sciences, 2017)
Background: Being a maladaptive means of coping with stress, alcohol abuse may be associated with level of terrorism in a community. Jos has had a number of terrorists’ attacks which have had devastating effects on the city and its environs. This study aimed to determine the prevalence of terrorism catastrophizing, hazardous alcohol use as well as the relationship between terrorism catastrophizing and hazardous alcohol use among students of the Plateau State Polytechnic, Jos Campus. Methods: A cross sectional study of 230 students in the departments of accountancy, business administration and management who completed self-administered questionnaires during one of their classes following a random cluster sampling of departments. Results: The TCS showed that 43.5% of the participants had terrorism catastrophizing. Pearson correlation showed a high significant positive correlation (p<0.05) across the three dimensions of terrorism catastrophizing: rumination, r=0.807; magnification, r=0.726; and helplessness, r=0.754. However, no significant correlation exists between terrorism catastrophising (rumination, magnification and helplessness), alcohol use disorder, r = -0.016, p = 0.817 (AUDITc), and problem drinking behavior, r= -0.157, p=0.06. Conclusions: There was no positive correlation between terrorism catastrophizing and hazardous alcohol drinking.